Levantamento retrospectivo de casos de dermatite atópica canina atendidos no serviço de dermatologia veterinária do hospital veterinário da Faculdade de Medicina Veterinária e Zootecnia da UNESP - Botucatu (jan/2022 a out/2024) - Silva, André Castilhano Marcelino [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
A dermatite atópica canina (DAC) é uma síndrome clínica alergoinflamatória de caráter crônico e geneticamente herdada, de prevalência estimada entre 10 a 15% na população canina global. Foram selecionados prontuários médicos veterinários de cães atendidos no serviço de Dermatologia Veterinária do Hospital Veterinário da Faculdade de Medicina Veterinária e Zootecnia da UNESP - Botucatu, durante os 34 meses de janeiro de 2022 a outubro de 2024, com diagnóstico de dermatite atópica. No período, foram atendidos 2.141 animais no serviço de Dermatologia Veterinária e, destes, 206 (9,6%) foram diagnosticados com dermatite atópica. Desses, 63,1% eram fêmeas, 73,3% tinham menos de 3 anos de idade, e tiveram alta representatividade racial de Shih-tzu (28,2%) e Sem Raça Definida (22,3%) entre os cães acometidos. As patas foram acometidas em 90,3% e os condutos auditivos em 77,7% dos animais do levantamento e, portanto, foram as regiões corporais mais acometidas no levantamento. A intensidade do prurido tendeu a ter notas mais elevadas na escala analógica visual do prurido, com 89,8% dos tutores relatando nota de 5 pontos ou mais. O prurido foi não sazonal em 82,5% dos casos e 86% dos animais viviam em ambiente domiciliar interno. Os tutores já haviam administrado corticosteroides e oclacitinib em, 40,3% e 20,4% dos animais, respectivamente. Em relação à resposta clínica ao uso medicamento, 72,3% apresentaram resposta satisfatória ao uso do corticoide e 62% de resposta satisfatória ao uso de oclacitinib.

Canine atopic dermatitis (CAD) is a chronic and genetically inherited allergo-inflammatory clinical syndrome, with an estimated prevalence of between 10 and 15% in the global canine population. Veterinary medical records of dogs treated at the Veterinary Dermatology service of the Veterinary Hospital of the Faculty of Veterinary Medicine and Zootechnics of UNESP - Botucatu, during the 34 months from January 2022 to October 2024, with a diagnosis of atopic dermatitis were selected. During the period, 2,141 animals were treated at the Veterinary Dermatology service and, of these, 206 (9.6%) were diagnosed with atopic dermatitis. Of these, 63.1% were female, 73.3% were less than 3 years old, and there was a high racial representation of Shih-tzu (28.2%) and No Defined Breed (22.3%) among the affected dogs. The paws were affected in 90.3% of the animals in the survey, and the ear canals were affected in 77.7% of the animals in the survey. Therefore, the body regions were most affected in the study. Itching intensity tended to have higher scores on the visual analog itch scale, with 89.8% of owners reporting a score of 5 points or more. The itching was non-seasonal in 82.5% of cases and 86% of animals lived indoors. The owners had already administered corticosteroids and oclacitinib to 40,3% and 20,4% of the animals, respectively. Regarding the clinical response to medication use, 72.3% had a satisfactory response to the use of corticosteroids, and 62% had a satisfactory response to the use of oclacitinib.
Retrospective survey of cases of canine atopic dermatitis treated at the veterinary dermatology service of the Veterinary Hospital of the Faculty of Veterinary Medicine and Zootechnics at UNESP - Botucatu (jan/2022 to oct/2024)
Keywords: Atopia; Prurido; Dermatopatia; Atopy; Pruritus; Dermatopathy